1–10–100: Unifying goals to mobilize global action on antimicrobial resistance - Katwyk, S.R.V.; Poirier, M.J.P.; Chandy, S.J.; Faure, K.; Fisher, C.; Lhermie, G.; Moodley, Arshnee; Sarkar, S.; Masika, S.; Strong, K.; Weldon, I.; Hoffman, S.J. (Springer, 2024)
The Bellagio Group for Accelerating AMR Action met in April 2024 to develop the ambitious but achievable 1–10-100 unifying goals to galvanize global policy change and investments for antimicrobial resistance mitigation: 1 Health; 10 million lives saved; and 100% sustainable access to effective antimicrobials. High profile political goals such as the Paris Agreement’s objective to keep global warming well below 2° Celsius compared to pre-industrial levels, UNAIDS’ 90–90-90 goal, and the Sustainable Development Goals challenge global norms, direct attention towards relevant activities, and serve an energizing function to motivate action over an extended period of time. The 1–10-100 unifying goals propose to unite the world through a One Health approach to safeguard human health, animal welfare, agrifood systems, and the environment from the emergence and spread of drug-resistant microbes and infections; save over 10 million lives by 2040 through concerted efforts to prevent and appropriately treat infections while preserving the vital systems and services that depend on sustained antimicrobial effectiveness; and commit to ensuring that antimicrobials are available and affordable for all, used prudently, and secured for the future through innovation. Compared to existing technical targets, these unifying goals offer advantages of focusing on prevention, encouraging multisectoral action and collaboration, promoting health equity, recognizing the need for innovation, and integrating with Sustainable Development Goals. By committing to 1 Health, 10 million lives saved, and 100% sustainable access to effective antimicrobials, we can protect lives and livelihoods today and safeguard options for tomorrow.